ANALISIS WAKTU TEMPUH PERJALANAN KENDARAAN RINGAN DI KOTA SAMARINDA - SAPUTRA, RIYAN EKO (KURVA S JURNAL MAHASISWA, 2015)
Time travel (Travel Time) defined the total time required to pass through a certain path length, including time stops and delays at intersections. And Cost of Operations Vehicle (COV) is a great value expressed his charge is issued for the operator of a vehicle under normal conditions for a particular purpose.The objectives to be achieved in this research is knowing the speed of light vehicles on the road Abul Hasan - P. Diponegoro - P. Hidyatullah - P. Suriansyah - Yos Sudarso - Gajah Mada - RE. Sana, Knowing the travel time of light vehicles on the road Abul Hasan - P. Diponegoro - P. Hidyatullah - P. Suriansyah - Yos Sudarso - Gajah Mada - RE. Sana, Knowing the value of the vehicle operational costs (COV).The method used for data retrieval using stopwacth travel time, while the data for the analysis of travel time and speed using MKJI 1997, while the operational costs of vehicles using the PCI (Pacific Consultant International). From the calculation results can be concluded that there is a late trip on elephant mada-lane road section II with an average speed of 20.31 km/h the vehicle operational cost Rp. 6644 / kmÂ